2020
DOI: 10.1159/000510984
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Is Associated with Cardiac Biomarkers, Echocardiographic Indices, and Mortality in CKD Stage 4–5 Patients Not on Dialysis

Abstract: <b><i>Introduction:</i></b> Patients with CKD have an impaired health-related quality of life (QoL). Most studies have been conducted on dialysis patients, and less is known about QoL and its determinants in predialysis patients. We studied the association between QoL and comorbidities, cardiac biomarkers, echocardiography, and mortality in patients with CKD stage 4–5 not on dialysis. <b><i>Methods:</i></b> A total of 140 patients enrolled in the Chronic Arterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(31 reference statements)
2
2
0
Order By: Relevance
“…Our current results suggest that increased TnT in CKD is a determinant of cardiovascular burden that affects the day to day life of patients with advanced CKD by limiting their maximal physical performance in addition to increasing their risk for incident cardiovascular death. In accordance with this finding we have previously shown that the physical composite score of the Short Form 36 Items Health Survey (SF-36 QOL) is inversely associated with TnT in the CADKID study population [21].…”
Section: Discussionsupporting
confidence: 81%
“…Our current results suggest that increased TnT in CKD is a determinant of cardiovascular burden that affects the day to day life of patients with advanced CKD by limiting their maximal physical performance in addition to increasing their risk for incident cardiovascular death. In accordance with this finding we have previously shown that the physical composite score of the Short Form 36 Items Health Survey (SF-36 QOL) is inversely associated with TnT in the CADKID study population [21].…”
Section: Discussionsupporting
confidence: 81%
“…Few QoL studies have utilized echocardiographic data. We previously demonstrated an association between PCS and left ventricular systolic and diastolic function in echocardiography [7]. In the present follow-up study, mean EF was the only variable independently associated with dPCS in multivariable analysis.…”
Section: Discussionsupporting
confidence: 56%
“…No power calculations were performed as there are no previous data on the development of QoL in nondialysis CKD stage 4-5 patients transitioning to different RRT modalities. The baseline data for QoL measures in the CADKID study population have been reported earlier [7]. According to the original study plan reported at clinicaltrials.gov, re-assessment of QoL was scheduled to be performed 2 years after the first assessment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation